2021
DOI: 10.18502/ijm.v13i5.7425
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sphingomonas paucimobilis as an emerging nosocomial pathogen in a teaching hospital in Uttarakhand

Abstract: Background and Objectives: Sphingomonas paucimobilis is an opportunistic pathogen and was rarely encountered in clin- ical specimens previously. This study aimed to investigate the clinical features, associated co-morbidities, and antimicrobial susceptibility patterns of S. paucimobilis infection in a tertiary hospital in Uttarakhand. Materials and Methods: S. paucimobilis isolates cultured from various sections of hospital and OPDs were identified and an- alyzed for their antibiograms in the microbiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…2,9 This infection is usually seen in immunocompromised states like malignancies, steroid use, immunodeficiencies, or chronic disease states like diabetes mellitus, chronic kidney disease, or chronic respiratory conditions. [1][2][3][4] According to a retrospective study done by Rohilla in a teaching school in Uttarakhand, diabetes mellitus and steroid use were the most common comorbid conditions in which S. paucimobilis infection was seen. 3 Such patients commonly have a contact history with healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2,9 This infection is usually seen in immunocompromised states like malignancies, steroid use, immunodeficiencies, or chronic disease states like diabetes mellitus, chronic kidney disease, or chronic respiratory conditions. [1][2][3][4] According to a retrospective study done by Rohilla in a teaching school in Uttarakhand, diabetes mellitus and steroid use were the most common comorbid conditions in which S. paucimobilis infection was seen. 3 Such patients commonly have a contact history with healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] According to a retrospective study done by Rohilla in a teaching school in Uttarakhand, diabetes mellitus and steroid use were the most common comorbid conditions in which S. paucimobilis infection was seen. 3 Such patients commonly have a contact history with healthcare facilities. A retrospective study by Ionescu et al showed that at least 43% of patients with bloodstream infections had a hospital-acquired infection and 37% had acquired one from the community.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations